2012
DOI: 10.1002/cyto.a.22058
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent response to long‐term storage in liquid‐preserved boar semen: A flow cytometric analysis

Abstract: The fertility of liquid-preserved boar semen declines during storage at 178C, insemination trials even indicating early losses in fertilizing ability within the first 24-48 h of storage. Standard semen parameters barely reflect these changes in semen quality, and new approaches for assessment of functional changes in stored spermatozoa are needed. Capacitation, the essential prefertilization step for spermatozoa in the female genital tract, is specifically induced in vitro by bicarbonate. Therefore, we have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…Moreover, conventional sperm parameters used to test the quality of boar semen doses mostly are too insensitive to assess the fertilization potential of liquid stored semen (Waberski et al, 2011). In recent studies, effort has been focused to test whether spermatozoa membranes retain their ability to respond to oviductal signals, considering dynamic responses in spermatozoa under experimentally mimicked fertilizing conditions (Henning et al, 2012;Petrunkina et al, 2005a). Several studies have indicated that a certain subpopulation of boar spermatozoa may loose their responsiveness to the capacitating stimulus bicarbonate during hypothermic storage (Green & Watson, 2001;Guthrie & Welch, 2005;Harrison et al, 1996;Petrunkina et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, conventional sperm parameters used to test the quality of boar semen doses mostly are too insensitive to assess the fertilization potential of liquid stored semen (Waberski et al, 2011). In recent studies, effort has been focused to test whether spermatozoa membranes retain their ability to respond to oviductal signals, considering dynamic responses in spermatozoa under experimentally mimicked fertilizing conditions (Henning et al, 2012;Petrunkina et al, 2005a). Several studies have indicated that a certain subpopulation of boar spermatozoa may loose their responsiveness to the capacitating stimulus bicarbonate during hypothermic storage (Green & Watson, 2001;Guthrie & Welch, 2005;Harrison et al, 1996;Petrunkina et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that a certain subpopulation of boar spermatozoa may loose their responsiveness to the capacitating stimulus bicarbonate during hypothermic storage (Green & Watson, 2001;Guthrie & Welch, 2005;Harrison et al, 1996;Petrunkina et al, 2005b). Henning et al (2012) showed that the comparison of calcium-dependent spermatozoa responses between three different media, capacitating Tyrode's medium, (including calcium and bicarbonate), bicarbonate-free Tyrode's medium and calcium-and bicarbonate-free medium, sensitively detected storage-related changes in the spermatozoa population. Our results show that previous incubation in the presence of RSV 33 µM is unable to revert the decline in the response to bicarbonate and therefore the increasing inherent instability brought about by liquid storage time of boar semen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations